STUDI TENTANG PEMBINAAN AKHLAKUL KARIMAH SANTRI DI PONDOK PESANTREN DDI MANGKOSO, SULAWESI SELATAN - Jumrianah Jumrianah (Al-Rabwah, 2019)
This study aims to determine the efforts of teachers in fostering the morals of students at the DDI Magkoso boarding school and to determine the factors that influence the morals of the students at the DDI Mangkoso boarding school. The population from this study are all coaches of DDI Mangkoso Islamic Boarding School, Barru District. Researcher took all of DDI Mangkoso Islamic Boarding School coaches as population, in Islamic Boarding School, Barru District with 20 people, with the consideration of the very small number. Thus, this study is a population study. this study, using interview guidelines, observation guidelines with a questionnaire as a research instrument. This is intended to obtain accurate and accountable data. the final step to conclude the data from the research results is to analyze all the data that has been obtained. With reference to this, the authors use qualitative techniques. The result from this study expalined that moral development in Islamic Boarding school Barru by giving memorization habituation, giving role models and verbally teaching noble morals both in the habituation of religious morals and in social life. The process of fostering morality in the students at the boarding school DDI Mangkoso carried out in various forms of memorization of prayers and prayers, memorizing juz amma, memorizing certain letters in the Qur'an, memorizing the ablution prayers and prayers, memorizing recitations in prayers in congregation , sunnah prayers, tahlil and grave pilgrimage, maintaining cleanliness, training in speeches, speaking and planting commendable qualities and activities that are accompanied by moral guidance material on God, towards fellow human beings and towards nature or the environment